The giraffe and the pelly and me - Dahl, Roald, 1916-1990.; Blake, Quentin; Puffin Books (London : Puffin Books, 2001)
A small boy with a desire to own a candy shop meets a window-washing team composed of a giraffe, a pelican, and a monkey and together they go to work for the wealthy Duke of Hampshire, who makes all their dreams come true.
4.7
3-6
Keywords: Candy -- Juvenile fiction; Giraffe -- Juvenile fiction; Monkeys -- Juvenile fiction; Pelicans -- Juvenile fiction; Candy -- Fiction; Giraffe -- Fiction; Monkeys -- Fiction; Pelicans -- Fiction; Giraffes -- Fiction